Juvenile Drug Offenses and Legal Handling in Sidoarjo Police: Pelanggaran Narkotika oleh Anak di Bawah Umur dan Penanganan Hukum di Kepolisian Sidoarjo - Ladita, Firrisa Farah; Rosnawati, Emy (Indonesian Journal of Law and Economics Review, 2025)
General Background: Drug abuse remains a major social and legal issue in Indonesia, affecting not only adults but also children. Specific Background: The increasing involvement of minors in narcotics-related crimes demands a legal approach that balances justice and rehabilitation. Knowledge Gap: However, limited empirical insight exists regarding how law enforcement officers implement child-specific justice systems in handling narcotics cases. Aims: This study aims to analyze the enforcement of drug laws against minors at the Sidoarjo Police Department and to examine the distinction in legal processes between juvenile and adult offenders. Results: Findings reveal that while penalties for drug distribution are consistent across age groups under Law No. 35 of 2009, the judicial process for minors follows the Child Protection Law and the Juvenile Criminal Justice System, which reduce sentences by one-third and prioritize rehabilitation. Novelty: This study provides a socio-legal understanding of law enforcement that emphasizes rehabilitation rather than punishment for minors. Implications: The results encourage transparency, humanistic approaches, and inter-agency collaboration to improve juvenile narcotics case handling and strengthen child protection within the justice system. <article class="text-token-text-primary w-full focus:outline-none [–shadow-height:45px] has-data-writing-block:pointer-events-none has-data-writing-block:-mt-(–shadow-height) has-data-writing-block:pt-(–shadow-height) [&:has([data-writing-block])>*]:pointer-events-auto [content-visibility:auto] supports-[content-visibility:auto]:[contain-intrinsic-size:auto_100lvh] scroll-mt-[calc(var(–header-height)+min(200px,max(70px,20svh)))]" dir="auto" tabindex="-1" data-turn-id="request-WEB:9be31cf0-d04b-44df-8366-5ea48d538e8e-18" data-testid="conversation-turn-4" data-scroll-anchor="false" data-turn="assistant"> <div class="[–thread-content-max-width:40rem] thread-lg:[–thread-content-max-width:48rem] mx-auto max-w-(–thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn" tabindex="-1"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal [.text-message+&]:mt-1" dir="auto" data-message-author-role="assistant" data-message-id="bc11c78c-3e0a-4a0d-99c6-a1d80c56acfe" data-message-model-slug="gpt-5"> Highlights: Juvenile offenders receive reduced and rehabilitative legal treatment. Law enforcement applies a distinct process for minors under SPPA Law. Study reinforces humane and transparent handling of drug abuse cases. Keywords: Juvenile Justice, Drug Abuse, Law Enforcement, Rehabilitation, Child Protection